STUDY THE PATHOLOGICAL EFFECTS OF Klebsiella pneumoniae ISOLATED FROM LUNGS OF PNEUMONIA'S INFECTED SHEEP AND EXPERIMENTALLY INFECTED IN MICE - Muna Sachit Hashim; Zahra Saleh Mahdi; Taghreed Jabbar Humadi; Eman Hashim Yousif; Thikra Abdulla Mahmood (Basrah Journal of Veterinary Research)
Currents study was designed to investigations about Klebsiella pneumoniaeinfection in sheep then evaluation its effects in mouse by experimentally infectionField study conducting on examination of one hundred100 sheep's lungs in KerbalaProvince, these lungs were send to laboratory of microbes for microbial examine.Results showed 44 % of lungs samples were infected with Klebsiella pneumoniae;18% of samples were negative for bacterial examination and the others 38 sampleswere infected with different type of bacteria but not frequently occurs as Klebsiella eLaboratory study, the isolated Klebsiella pneumoniae used to induce experimentalinfection in mice. Thirty 30 mixed mice at age of (4-6) weeks were used andsubdivided in to three 3 group; 1st contains 10 ten males injected with 0.25ml.IP. (1.5*10) suspension of bacteria; 2nd contains 10 ten females injected with 0.25ml.IP. (1.5*10) suspension of bacteria; 3rd contains mixed ten mice injected with Distilled Water.Scarified 4 four animals were done at the end of one week's until last 4 four week.Samples of tissues (liver, Kidney, lung, spleen, testes, uterus) were taken from eachmouse. Maine pathological lesions in lung of sheep infected with Klebsiellapneumoniae were suppurative broncho pneumonia, giant cell infiltration andgranulomatous foci. Tissues samples of experimentally infected mice showed generalabscesses at 1-2 weeks of infection, necrosis with granuloma and giant cell infiltrationat 3-4 weeks of infection. Conclusion: Klebsiella pneumoniae infects lung sheep and cause chronic suppurative pneumonia due to presence of giant cell as well asexperimentally infects mice and causes general suppurative and granulomatouslesions